A systemic view on autonomous vehicles. Policy aspects for a sustainable transportation planning. - Bahamonde-Birke, Francisco J.; Kickhöfer, Benjamin; Heinrichs, Dirk; Kuhnimhof, Tobias (Routledge, 2018)
Over the past few years, many studies have provided detailed descriptions of the potential benefits associated with the introduction of autonomous vehicles, such as improvements in traffic flows, local and global emissions, traffic safety, cost efficiency of public and private transport operations, etc. Additionally, the mobilization of mobility-impaired people and the independent car use of travelers without a driver's license have been identified as potential benefits for users. However, merely estimating the benefits of these direct effects is unlikely to show the full picture of the consequences that will emerge once autonomous vehicles enter the roads. In this paper are therefore discussed systemic effects. The paper presents a conceptual exploration of these effects based on literature and research findings to date. These systemic effects have the potential - especially in urban areas and without adequate policy intervention - to eliminate at least some of the benefits initially associated with autonomous vehicles.
Keywords: Verkehr; Autoverkehr; Automatisierung; Verkehrstechnik; Verkehrssystem; Verkehrsablauf; Reisezeit; Verkehrspolitik; Verkehrsplanung; Autonomes Fahren; Kraftfahrzeugverkehr; Fahrzeit; Verkehrsforschung